Associations between alcohol dehydrogenase genes and alcohol use across early and middle adolescence: Moderation × Preventive intervention. (23rd May 2017) - Cleveland, H. Harrington; Schlomer, Gabriel L.; Vandenbergh, David J.; Wolf, Pedro S. A.; Feinberg, Mark E.; Greenberg, Mark T.; Spoth, Richard L.; Redmond, Cleve
Abstract: Data from the in-school sample of the PROSPER preventive intervention dissemination trial were used to investigate associations between alcohol dehydrogenase genes and alcohol use across adolescence, and whether substance misuse interventions in the 6th and 7th grades (targeting parenting, family functioning, social norms, youth decision making, and peer group affiliations) modified associations between these genes and adolescent use. Primary analyses were run on a sample of 1, 885 individuals and included three steps. First, we estimated unconditional growth curve models with separate slopes for alcohol use from 6th to 9th grade and from 9th to 12th grade, as well as the intercept at Grade 9. Second, we used intervention condition and three alcohol dehydrogenase genes, 1B ( ADH1B ), 1C ( ADH1C ), and 4 ( ADH4 ) to predict variance in slopes and intercept. Third, we examined whether genetic influences on model slopes and intercepts were moderated by intervention condition. The results indicated that the increase in alcohol use was greater in early adolescence than in middle adolescence; two of the genes, ADH1B and ADH1C, significantly predicted early adolescent slope and Grade 9 intercept, and associations between ADH1C and both early adolescent slope and intercept were significantly different across control and intervention conditions.